The evolving panorama of vascular access in the 21st century - Neyra, Nilda Roxana; Wazir, Shoaib (Frontiers in Nephrology, 2022)
Abstract There are three major types of hemodialysis vascular access: hemodialysis catheters, arteriovenous grafts, and arteriovenous fistulas. Arteriovenous fistulas are the best accesses due to their reliability and long-term patency. They are recommended by current guidelines; however, not all patients benefit from arteriovenous fistulas due to poor maturation or lack of adequate vasculature. On the other hand, the majority of patients initiate hemodialysis via catheters, which are associated with higher morbidity and mortality due to infection and the development of central vein stenosis. Patients’ varied responses to different access types exemplify the need to choose the “right access for the right patient'' based on scores that can predict death risk and progression of chronic kidney disease. Additionally, vascular access, often referred to as the “Achilles’ heel” of hemodialysis patients, represents a significant percentage of the Medicare budget that continues to increase yearly. The purpose of this paper is to review the current literature on management of vascular access complications and infection treatment and prevention. The paper also explores emerging research regarding devices and methods to improve access outcomes such as early cannulation arteriovenous grafts, endovascular arteriovenous fistula creation, and regenerative grafts with resorbable scaffolds, among others. 1 Arizona Kidney Disease and Hypertension Center, (AKDHC) Phoenix AZ, USA 2 AKDHC Interventional Nephrology Fellow Corresponding author: N. Roxana Neyra MD, FACP. AKDHC 3320 N 2nd Street Suite 100, Phoenix, AZ 85012 Email: rneyra@akdhc.com